EXECUTIVE NETWORK OF POWER IN THE SYSTEM OF GOVERNMENTAL DIVISION - Rahimov Humoyun Otanazar o‘g‘li (Scholar Express Journals, 2023)
This thesis emphasizes the tasks that the Constitution of the Republic of Uzbekistan performs within the competence of the Cabinet of Ministers, which exercises executive powers.
Keywords: Executive authority; Cabinet of Ministers; Constitution; authority